2017
DOI: 10.1109/access.2017.2755984
|View full text |Cite
|
Sign up to set email alerts
|

Role of Self-Heating and Polarization in AlGaN/GaN-Based Heterostructures

Abstract: The interplay of self-heating and polarization affecting resistance is studied in AlGaN/GaN Transmission Line Model (TLM) heterostructures with a scaled source-to-drain distance. The study is based on meticulously calibrated TCAD simulations against I-V experimental data using an electrothermal model. The electro-thermal simulations show hot-spots (with peak temperature in a range of ∼ 566 K -373 K) at the edge of the drain contact due to a large electric field. The electrical stress on Ohmic contacts reduces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The simulations of 4H‐SiC MOSFET are carried out using the drift‐diffusion (DD) transport mode, Poisson equation and heat transport equation [7, 8]. These equations allow the calculation of electrostatic potential, the concentrations of electrons and holes, current and lattice temperature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The simulations of 4H‐SiC MOSFET are carried out using the drift‐diffusion (DD) transport mode, Poisson equation and heat transport equation [7, 8]. These equations allow the calculation of electrostatic potential, the concentrations of electrons and holes, current and lattice temperature.…”
Section: Methodsmentioning
confidence: 99%
“…At a low field, we used analytic mobility which is based on Caughey–Thomas [7, 10, 11] μnfalse(n,TnormalLfalse)=μ1TL300a+μ2false(TnormalL/300false)bμ1false(TnormalL/300false)a1+false(TnormalL/300false)cfalse(n/NCRfalse)d where n is the total doping concentration; T L is the lattice temperature in Kelvin; μ1 and μ2 are the mobilities of undoped samples; NCR is the doping concentration when the mobility has an average value between μ1 and μ2; d shows the rate of changing mobility from μ1 to μ2; and a , b , c and d are temperature‐dependent coefficients [7, 10, 11].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Simin G. et al [10] revealed that gate bias-induced inhomogeneous strain in the AlGaN barrier will cause a decrease in polarization charge and reduction in 2DEG in normally-on HEMT device by experiments. Ahmeda K. et al [11] found that applying strain in drain region will cause changes in the total polarization, thus affecting 2DEG density in the channel. However, as far as we known, there are few reports on the strain effect in the AlGaN barrier of normally-off HEMT with a p-GaN gate.…”
Section: Introductionmentioning
confidence: 99%